The inimitable outsider: contracting out public affairs from a consultant's perspective - Hoffmann, Jochen; Steiner, A.; Jarren, O. (Emerald Group Publishing Ltd, 2011)
Purpose – Academic research on public affairs which aims to reconstruct the rationale for the involvement in public affairs, and the possible outsourcing thereof, focuses mainly on the perspective of the principal. Even though consultants are undoubtedly increasing in importance, their relevance as agents is often downplayed. This study seeks to empirically supplement the perspective of the consultant in order to identify potential inimitable functions that could explain why public affairs work is often contracted-out. Design/methodology/approach – A nation-wide survey about public affairs consultants in Switzerland is based on an inductive empirical research design, which facilitates questions regarding which services consultants actually perform and what indispensable functions they claim to provide. Findings – The results highlight lobbying, political PR, and [referendums and election] campaigns as the main areas of service. These services are associated with different functions. Lobbyists in particular define themselves as partisan players closely involved in political decision making. In contrast, political PR and campaigning are understood in terms of horizontal or vertical boundary-spanning. A somewhat technical justification for contracting out, referring to a special infrastructure and costs issues, is downplayed. Instead, the independent outside view facilitating innovation forms the most important generalizable frame when explaining the unique added value consultants have to offer. Originality/value – The paper shows that the real or supposed independence of the consultant vis-a` -vis the client constitutes an inimitable resource. The outsider-status facilitates the successful fulfilment of public affairs functions such as innovation, boundary-spanning, access and legitimising. Thus, it is vitally important for consultants to build up a reputation. When it comes to contracting-out decisions, impression management theories are capable of enriching public affairs theories that focus on cost-benefit-calculations.